2012
DOI: 10.5402/2012/704825
|View full text |Cite
|
Sign up to set email alerts
|

Trace Minerals and Livestock: Not Too Much Not Too Little

Abstract: The new approaches of the animal production systems make managing the mineral nutrition a challenge. Versus the excessive, trace mineral supply in intensively managed livestock, well above the physiological requirements, is the no trace mineral supplementation of organic systems, which become highly dependent on trace minerals in the soil. Nowadays, in addition to the animal health perspective, trace mineral nutrition must be environment friendly and allow getting mineral-enriched animal products. We are in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 99 publications
2
102
0
5
Order By: Relevance
“…This monitoring was carried out in JSC Chervlenoye and JSC Oblomovo of the Svetloyarsky area, which is the most ecologically unsuccessful southern part of a residential suburb of Volgograd. The dynamics of industrial parameters of that period are similar to the current systemic crisis caused by the global, politiсal and economic reasons, and having a tendency to develop further (López-Alonso, 2012). Along with monitoring the livestock production, the quantitative chemical and toxicological analyses were also performed: 30 exemplars of the soil -for 26 indicators; 22 exemplars of water -for 18 indicators; 98 exemplars of forage (26 species of plants) -for 17 indicators; 55 exemplars of blood -for 17 measures; 18 exemplars of wool -for 40 indicators; 34 exemplars of products of slaughter -for 12 indicators; 76 exemplars of milk -for 57 indicators.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…This monitoring was carried out in JSC Chervlenoye and JSC Oblomovo of the Svetloyarsky area, which is the most ecologically unsuccessful southern part of a residential suburb of Volgograd. The dynamics of industrial parameters of that period are similar to the current systemic crisis caused by the global, politiсal and economic reasons, and having a tendency to develop further (López-Alonso, 2012). Along with monitoring the livestock production, the quantitative chemical and toxicological analyses were also performed: 30 exemplars of the soil -for 26 indicators; 22 exemplars of water -for 18 indicators; 98 exemplars of forage (26 species of plants) -for 17 indicators; 55 exemplars of blood -for 17 measures; 18 exemplars of wool -for 40 indicators; 34 exemplars of products of slaughter -for 12 indicators; 76 exemplars of milk -for 57 indicators.…”
Section: Methodsmentioning
confidence: 77%
“…A strict definition of heavy metals and arsenic in sterns of a winter and summer diet of lactic breeds of cattle confirmed that different types of plants possess unequal ability to absorb and accumulate these heavy metals and arsenic, and also lack of a feedforward between the level of pollution and intensity of intake of metals in plants (Zelepukhin, Levahin, 2000;López-Alonso, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Problems associated with mycotoxins in silage can be minimized by preventing fungal growth before and after ensiling. Proper silage management is essential and must be the first step in preventing/reducing the mycotoxin contamination of dairy cow feeds [55,57]. However, warm and humid weather conditions make it very difficult to control contamination without the use of mold-inhibiting feed additives such as mycotoxin binders used either in the silage or in the Total Mixed Ration (TMR).…”
Section: The Benefit Of Using Feed Supplements: Why the Feed Industrymentioning
confidence: 99%
“…Copper has been related to an increased resistance to mastitis (one of the most relevant problems in dairy farms) [54], particularly that caused by Escherichia coli. López-Alonso [55] reviewed the importance of trace mineral nutrition in organic livestock farming and found that the use of chemical forms of minerals (such as organic minerals/chelates) that are effective in production performance and health must be considered. Trace minerals are chemically bound to a chelating agent or ligand, usually a mixture of amino acids or small peptides.…”
Section: The Benefit Of Using Feed Supplements: Why the Feed Industrymentioning
confidence: 99%
“…Hence, selenomethionine is absorbed and metabolized relative to methionine needs. If selenomethionine is broken down within the cell, Se is released and recognized by the cell as a mineral [29]. It is then processed according to the need for Se.…”
Section: Selenium Absorption Distribution and Metabolic Fatementioning
confidence: 99%